ホッキョクケン ニオケル ニッポン・スウェーデン コクサイ キョウドウ バルーン・ロケット カンソク ケイカク g. ショウライ ケイカク ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 鎌田, 哲夫; カマタ, テツオ; 石川, 晴治; イシカワ, セイジ; 小玉, 正弘; コダマ, マサヒロ; 伊藤, 富造; イトウ, トミゾウ; 福西, 浩; フクニシ, ヒロシ; KAMATA, Tetsuo; ISHIKAWA, Seiji; et al. (1980)
P(論文) 中間圏と電離圏,電離圏と磁気圏のカップリングの問題を究明するには,高緯度帯で,地上観測設備,バルーン,ロケット,衛星を使って,波動,粒子,電場,磁場の総合観測を実施することがきわめて重要である.このために,今回北極圏における日本・スウェーデン国際協同観測を立案し,スウェーデンのEsrange(67°53'N,21°04'E)を観測地に選定した.ここは,宇宙空間から大気圏へ進入してくる荷電粒子によって誘起されるさまざまな現象を観測するのにもっとも適した場所だからである.ここでは,この総合観測計画を紹介する. In order to investigate problems of coupling between the middle atmosphere and the ionosphere, and also between the ionosphere and the magnetosphere, it is very important to carry out comprehensive observations of waves, partides, electric field and magnetic field in a high latitude region by a ground-based station, a balloon, a rocket and a satellite. For that purpose, the observation by the international cooperation between Japan and Sweden is planned in the Arctic region. Esrange (67°53'N, 21°O4E) in Sweden is chosen as the observation place, because it is ideally situated for observing various phenomena caused by charged particles coming from space to enter the atmosphere. In this paper, the comprehensive observation plan is described. departmental bulletin paper